The Agrobiodiversity Diet Diagnosis Interventions Toolkit (ADD-IT) - Progress report - Nutrition Team in Kenya and Communications (Bioversity International, 2018)
This factsheet is a brief progress report on the Agrobiodiversity Diet Diagnosis Interventions Toolkit, which will improve nutrition intervention programmes by facilitating reliable data collection, management, and more informed decision-making. The distinct feature of the tool is that it promotes sustainable use of locally available agrobiodiversity to improve nutrition, health and livelihoods.